2017
DOI: 10.1371/journal.pone.0184154
|View full text |Cite
|
Sign up to set email alerts
|

SCF-KIT signaling induces endothelin-3 synthesis and secretion: Thereby activates and regulates endothelin-B-receptor for generating temporally- and spatially-precise nitric oxide to modulate SCF- and or KIT-expressing cell functions

Abstract: We demonstrate that SCF-KIT signaling induces synthesis and secretion of endothelin-3 (ET3) in human umbilical vein endothelial cells and melanoma cells in vitro, gastrointestinal stromal tumors, human sun-exposed skin, and myenteric plexus of human colon post-fasting in vivo. This is the first report of a physiological mechanism of ET3 induction. Integrating our finding with supporting data from literature leads us to discover a previously unreported pathway of nitric oxide (NO) generation derived from physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 151 publications
(209 reference statements)
1
2
0
Order By: Relevance
“…Previous studies have ICC injury in the colons of patients and rats with FC (12,45). The present results revealed that C-Kit and SCF were mainly present in the submucosa and muscle layers, which is consistent with previous studies (46,47). Furthermore, a novel finding of the present study was that Arc prevented the increase in damage and increased the density of ICC in the colon of FC mice.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have ICC injury in the colons of patients and rats with FC (12,45). The present results revealed that C-Kit and SCF were mainly present in the submucosa and muscle layers, which is consistent with previous studies (46,47). Furthermore, a novel finding of the present study was that Arc prevented the increase in damage and increased the density of ICC in the colon of FC mice.…”
Section: Discussionsupporting
confidence: 93%
“…EDNs exert their functions by interacting with their cognate receptors (ETAR and ETBR), thus mediating fundamental processes in tissue differentiation, repair and growth ( 45 ). EDN1 and EDN3 primarily interact with ETAR and ETBR, respectively ( 46 ). EDN1 has been reported to be produced by endothelial cells, vascular smooth muscle cells, epithelial cells, hepatocytes and neurons ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, EDN3 primarily originates from epithelial cells, adrenal cells and neurons ( 48 ). By interacting with ETb, EDN3 frequently affects EDN1 autoinduction, angiogenesis, inflammatory pain, endothelin clearance and vasodilation ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%